Modified inertia Halpern method for split null point problem in Banach spaces - ABASS, Hammed Anuoluwapo; UGWUNNADI, Godwin; NARAIN, Ojen (Studia Universitatis Babeș-Bolyai Mathematica, 2024)
In this paper, we study split null point problem in reflexive Banach spaces. Using the Bregman technique together with a modified inertial Halpern method, we approximate a solution of split null point problem. Also, we establish a strong convergence result for approximating the solution of the aforementioned problems. It is worth mentioning that the iterative algorithm employ in this study is design in such a way that it does not require prior knowledge of operator norm. We display some numerical examples to illustrate the performance of the proposed iterative method. The result discuss in this paper extends and complements many related results in literature. Mathematics Subject Classification (2010): 47H06, 47H09, 47J05, 47J25. Received 12 May 2022; Accepted 12 September 2022